MACiE (Mechanism, Annotation and Classification in Enzymes): novel tools for searching catalytic mechanisms - Holliday, Gemma L. (Oxford University Press, 2007)
MACiE (Mechanism, Annotation and Classification in Enzymes) is a database of enzyme reaction mechanisms, and is publicly available as a web-based data resource. This paper presents the first release of a web-based search tool to explore enzyme reaction mechanisms in MACiE. We also present Version 2 of MACiE, which doubles the dataset available (from Version 1). MACiE can be accessed from